2016
DOI: 10.1111/ajco.12474
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a brief exercise program on the physical and psychosocial health of prostate cancer survivors: A pilot study

Abstract: A four-session exercise program significantly improved the muscular strength, exercise capacity, physical function and positive well-being of prostate cancer survivors. This short-duration exercise program is safe and feasible for prostate cancer survivors and a randomized controlled trial is now required to determine whether a similar individualized exercise regimen improves physical health and mental well-being over the short, medium and long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 43 publications
1
9
0
2
Order By: Relevance
“…Interestingly, Bourke reported that this sense of masculine community required exercise program exclusivity. Men pointed to their need to feel safe and be surround by similar prostate cancer patients in order to express their feelings fully.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Interestingly, Bourke reported that this sense of masculine community required exercise program exclusivity. Men pointed to their need to feel safe and be surround by similar prostate cancer patients in order to express their feelings fully.…”
Section: Resultssupporting
confidence: 87%
“…42 Only two studies in this review instructed patients to supplement their group training with home-based aerobic activity; however, it is unclear whether guideline levels of activity were obtained. 25,27 Overall, there was a high level of agreement of masculine themes identified from these reviewed studies. This strengthens previous exercise and masculinity theories [26][27][28]38,39,43,44 and provides credibility to the emergent subthemes developed in this review.…”
Section: Because Of the Low Number Of Included Studies In This Reviewmentioning
confidence: 78%
See 2 more Smart Citations
“…Physical exercise is considered an essential factor for improving cancer survival. Previous studies have indicated that exercise interventions are efficacious in men with prostate cancer (41,42) and in multiple myeloma (43,44). In endometrial, ovarian and colorectal cancer survivors, lifestyle interventions that include regular participation in physical activity are associated with positive health outcomes (45,46).…”
Section: Discussionmentioning
confidence: 99%